Cambios en la articulación de la palabra en pacientes con oclusión clase III o mordida abierta anterior sometidos a cirugía ortognática - Velásquez-O., José Manuel; Radi-L., José N.; Hernández-V., Mauricio (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This study analyzed the changes that occurred in the articulation of oral phonemes (AP), the levels of stridence and hissing in patients with class III malocclusion and / or anterior open bite and that were subjected to orthognathic surgery. The sample consisted of 16 patients (12 females and 4 males), 12 of them were treated at the Stomatological and Maxillofacial Surgery Unit of the Hospital Universitario San Vicente de Paul, the other 4 were selected from private practice during the period of March and December 2001. The age range was between 16 and 37 years of age, with an average of 23,8 years. The sample included patients with class III malocclusion and / or anterior open bite that underwent orthognathic surgery. A Sound Forge 5.0® software, property of the radio station of University of Antioquia was used to look for changes in the articulation of various phonemes that imply dentoalveolar pronunciation. The results suggest that after the surgical correction of the skeletal discrepancies there is a positive change of the phonemes for the majority of patients.